Design of Temporary Storage for Hazardous and Toxic Waste in a Rotogravure Cylinder Manufacturing Industry - Aqil Azizi; Andy Rizky Pratama Siregar (Jurnal Serambi Engineering, 2023)
PT APEB is a company that producing rotogravure cylinders. Company's management of hazardous and toxic waste, commonly referred to as B3 waste has been inadequate, particularly in regards to the temporary storage facility. The aim of this study is to analyse the types, characteristics, and quantity of B3 waste produced by the company. The results will be used to design a temporary storage facility for B3 waste that complies with Indonesian standards. The method used in this study is descriptive quantitative. All of the collected data, including information on fire extinguishers, storage tanks, aperture area, lighting, pallets, and packaging, has been determined to aid in the development of a temporary storage facility for B3 waste that adheres to the current regulations in Indonesia. The building has been designed using the Sketchup software. The available space for the temporary B3 waste storage facility is 10 m x 10 m x 4.5 m, and it is divided into three parts: warehouse A (WWTP sludge), warehouse B (grinding sludge and PPE, rags, and contaminated packages), and warehouse C (electronic waste, chemical ex-lab, and oil waste), which are divided according to the type and characteristics of the waste. One dry chemical powder fire extinguisher is required for the building, along with 9 armature lights. Up to 5 pieces of ventilation with a length of 40 x 50 cm are also proposed.